1991
DOI: 10.1038/hdy.1991.44
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio, XY females and absence of inbreeding in a population of the Wood Lemming, Myopus schisticolor Lilljeborg, 1844

Abstract: In a Siberian population of the Wood Lemming a considerable excess of females has been observed for three subsequent years of low density. Female-biased sex ratio is associated with a high concentration of the X* chromosome which induces the development of X*Y specimens as females.The frequency of XY females was noticeably higher than that expected at equilibrium under random segregation of sex chromosomes in males and X*XOfemales. Estimates of F1 index were obtained from the frequencies of homozygotes and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…1995). Methods of trapping wood lemmings and the sampling design were described earlier (Gileva & Fedorov 1991;Fredga et ul. 1993).…”
Section: Methodsmentioning
confidence: 99%
“…1995). Methods of trapping wood lemmings and the sampling design were described earlier (Gileva & Fedorov 1991;Fredga et ul. 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The methods of lemming trapping and the design of the field study were described earlier (Gileva & Fedorov, 1991;Bondrup-Neilsen et a!., 1993).…”
Section: Methodsmentioning
confidence: 99%
“…First it was hypothesized that the female biased sex ratio is maintained by inbreeding, especially when the population density is low (Maynard Smith and Stenseth, 1978;Stenseth, 1978). However, isozyme studies showed that wood lemming populations are generally in HardyWeinberg equilibrium (HWE) (Fedorov, 1990(Fedorov, , 1991(Fedorov, , 1993Gileva and Fedorov, 1991;Fredga et al, 1993) indicating random mating.…”
Section: Introductionmentioning
confidence: 99%